PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS GOOGLE SITES TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Iryani, Risma; Muhisom; Siti Nuraini; Fadhilah Khairani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of fourth-grade elementary school students in Pancasila Education. It aimed to determine the effect of using Google Sites-based interactive media on students' learning outcomes in Pancasila Education. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of 37 fourth-grade students at UPTD SD Negeri 5 Metro Utara. The sample was selected using a nonprobability sampling technique with saturated sampling, in which Class IVA served as the experimental group and Class IVB as the control group. Data were collected through pretest-posttest assessments and student learning activity observation sheets, and were analyzed using simple linear regression and N-Gain analysis. The results indicated that the Google Sites-based interactive media had a significant effect on students' learning outcomes, with a significance value of 0.000 (< 0.05), indicating that the alternative hypothesis was accepted. Furthermore, the N-Gain analysis showed that the improvement in learning outcomes of the experimental group was higher than that of the control group.